Study of the composition of Pyracantha crenulata roem seed, oil and meal - Olinda E. Quiroga; Soledad M. Bou; Carlos I. Sarlingo; Susana M. Nolasco (Grasas y Aceites, 2003)
Seeds from Pyracantha crenulata Roem, harvested in Olavarría (Buenos Aires, Argentine) were defatted with hexane, obtaining raw oil with a yield of 5.5 % dry basis. The physicochemical characteristics of crude oil were: refractive index: 1.4770 (at 25ºC), iodine value: 121; saponification index: 203, unsaponifiable matter: 7.4 %, peroxide value: 8.7. The fatty acid composition of seed oil was studied by gas-liquid chromatography. Major fatty acids of seed oil were: linoleic (61.1 %), oleic (17.3 %) and palmitic acid (17.4 %). The residual seed meal contained low level of crude protein (13%, dry basis), considerable content of crude fiber and a relativity high value of neutral detergent fiber, that matching with the low digestibility observed. Metals, ash, sugar and polysaccharides contents are reported.